UMP ties up strategic collaboration with Elektrisola, Infineon - UMP, PNC
Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with Elektrisola (Malaysia) Sdn. Bhd. to foster a strategic collaboration in the fields ofacademic and research